2022
DOI: 10.3389/fphar.2022.965086
|View full text |Cite
|
Sign up to set email alerts
|

Open channel block of Kv1.5 channels by HMQ1611

Abstract: Kv1.5 channels conduct the ultra-rapid delayed rectifier potassium current (IKur). Pharmacological blockade of human Kv1.5 (hKv1.5) has been regarded as an effective treatment of re-entrant based atrial fibrillation, because Kv1.5 is highly expressed in human cardiac atria but scarcely in ventricles. The Kv1.5 blockade is also expected to be used in cancer therapeutics since Kv1.5 is overexpressed in some types of human tumors. Here, we investigated the blockade of hKv1.5 channels by HMQ1611, a symmetrical bip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…The selective blockage of hKv1.5 channels is considered as an effective treatment for re-entrant based atrial fibrillation. [95] In rat atrial muscles, psoralen was found to interact with hKv1.5 channels in their open state. The psoralen treatment produced voltage-dependent blockade of hKv1.5 channels and thus, escalated the rate of decay of hKv1.5 current.…”
Section: Antiarrhythmic Activitymentioning
confidence: 98%
See 1 more Smart Citation
“…The selective blockage of hKv1.5 channels is considered as an effective treatment for re-entrant based atrial fibrillation. [95] In rat atrial muscles, psoralen was found to interact with hKv1.5 channels in their open state. The psoralen treatment produced voltage-dependent blockade of hKv1.5 channels and thus, escalated the rate of decay of hKv1.5 current.…”
Section: Antiarrhythmic Activitymentioning
confidence: 98%
“…hKv1.5 channels are majorly expressed in atrial muscles of heart and are involved in conduction of ultra‐rapid delayed rectifier potassium current ( I kur ). The selective blockage of hKv1.5 channels is considered as an effective treatment for re‐entrant based atrial fibrillation [95] . In rat atrial muscles, psoralen was found to interact with hKv1.5 channels in their open state.…”
Section: Pharmacological Activities Of Psoralenmentioning
confidence: 99%